Students’ Strategies in Improving Their Reading Comprehension - Hendra Eka Putra; Nina Suzanne (Ta'dib, 2022)
The problem of this research was that there was no clear information about students’ strategies in improving their reading comprehension. Therefore, a descriptive quantitative method was used to find out the students’ strategies in improving their reading comprehension. A questionnaire consisting of 10 questions was distributed English Education Department students of IAIN Batusangkar to collect research data. The questionnaire was distributed to them, and there were 37 students who gave their responses. The data were analyzed by using descriptive statistical analysis. Based on the research results, it was found that there were three steps of reading strategies applied by students in improving their reading comprehension. In pre-reading stage, students applied six reading strategies: previewing, creating question, making prediction, writing the main points of what reader already know about the text, reading introductions and summaries, and creating a pre-reading outline strategy. The mostly applied strategy was previewing strategy, and the least one was reading introductions and summaries strategy. In whilst reading stage, they applied reading the selection text, visualizing, paraphrasing, elaborating, changing reading rate, inferring, note-taking, and rereading strategy. The mostly applied strategy was paraphrasing strategy, and the least one was rereading strategy. In the post-reading stage, students applied two reading strategies: summarizing and reviewing. Between both strategies, summarizing was dominantly applied.